2018
DOI: 10.1149/2.1351811jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Electrocatalyzed Oxygen Reduction at Manganese Oxide Nanoarchitectures: From Electroanalytical Characterization to Device-Relevant Performance in Composite Electrodes

Abstract: We assess the effect of the pore-solid architecture of cryptomelane-type manganese oxide (MnOx) xerogels and aerogels on electrocatalysis of the oxygen-reduction reaction (ORR) using three different electrochemical test platforms. Rotating-disk electrode measurements at ink-cast films of carbon + MnOx show that both MnOx nanoarchitectures exhibit comparable intrinsic ORR activity for four-electron reduction with a low onset overpotential (∼310 mV). The MnOx xerogel and aerogel powders were also incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[12][13][14][15][16] Because so many challenges must be solved to realize high-performance Zn batteries with Li-ion competitive cycle life, the characteristics of individual cell components-Zn anode, alkaline electrolyte composition, separators, cathodes (particularly for rechargeable Zn-air)-are often first evaluated with classical electroanalytical measurements in simplified cells or three-electrode configurations. Fundamental studies may provide valuable information, yet caution must be exercised when attempting to extrapolate results from such experiments to projected cell and pack performance, 17 particularly in the case of advances toward rechargeability.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…[12][13][14][15][16] Because so many challenges must be solved to realize high-performance Zn batteries with Li-ion competitive cycle life, the characteristics of individual cell components-Zn anode, alkaline electrolyte composition, separators, cathodes (particularly for rechargeable Zn-air)-are often first evaluated with classical electroanalytical measurements in simplified cells or three-electrode configurations. Fundamental studies may provide valuable information, yet caution must be exercised when attempting to extrapolate results from such experiments to projected cell and pack performance, 17 particularly in the case of advances toward rechargeability.…”
Section: Cycling Zinc Electrodes: Battery-relevant Testing or Fundamementioning
confidence: 99%
“…We previously showed that aerogel pore−solid architectures enhance electrocatalytic activity because they express amplified surface-to-bulk ratios and nanometric secondary particle sizes on the order of 10 nm. 29,30,57 An added benefit of aerogel materials is that they can be readily ground into fine powders, which disperse homogenously into the powder-composite electrode structures already used commercially for air cathodes. 57 The combination of a high active surface area and uniform distribution of the electrocatalyst within the conductive carbon/polymer matrix translates to improved electrochemical activity compared with conventionally prepared catalysts or those that form hard agglomerates but otherwise comprise nanoscale domains.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum power density with the Gortex membrane in place is 53 mW cm −2 at 0.95 V, whereas without the membrane present the cell delivers a maximum power density of 180 mW cm −2 at 0.73 V, a performance comparable to or higher than previously reported Zn−air cells using Mnbased catalysts for ORR. 57,66,67 These results indicate that for practical cells to operate at a higher power density than is typical with commercial Zn−air batteries (already considered "low"), one must improve not only cathode/catalyst performance but also O 2 flux and moisture management using advanced hydrophobic membranes. Potentiostatic impedance spectroscopy of a Zn−air cell containing a CC-Ni2Fe+Mn cathode was measured with a DC bias at specified voltages within a practical Zn−air battery discharge operation (1.3, 1.2, and 1.1 V).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations